First report of Strongyloides sp. (Nematoda, Strongyloididae) in Leopardus tigrinus (Carnivora: Felidae) in the municipality of Botucatu, State of São Paulo, Brazil - dos Santos, Karina R. [UNESP] (2009)
The present study reports the first case of infection by Strongyloides sp. in Leopardus tigrinus in the municipality of Botucatu, State of São Paulo, Brazil. Feces of the infected L. tigrinus specimen were cultivated in sterilized equine feces and a cat (Felis catus domesticus) was experimentally infected with three thousand infective L 3 subcutaneous route, in order to identify the Strongyloides species involved in the parasitism. Parthenogenetic females recovered from the experimental animals were analyzed but comparison between the biometric data found and the data in the literature did not enable identification of the species. This is the first report on the occurrence of Strongyloides sp. in L. tigrinus.